Using AppleWorks - Aron, Arthur; Aron, Elaine (Indiana : Que Corporation, 1989)
This book is organized so that you can learn only what need.
Part 1. The fundamentals -- Part 2. Appleworks word processor -- Part 3. Appleworks data base -- Part 4. Appleworks spreadsheet -- Part 5. Appleworks integration.
Includes index.
Keywords: APPLEWORKS (COMPUTER) -- PROGRAMMING